The Impact of Public-Private Partnerships on Infrastructure Investment and Economic Growth: A Comparative Study - Tryson Yangailo (Universitas Airlangga, 2026)
Objective: This study examines public-private partnership (PPP) investments in the infrastructure sectors of Brazil and China and their impact on economic growth. The study analyzes sector-specific investment behavior in water, energy, and transportation to determine its alignment with national development priorities and stages. The empirical analysis provides comparative insights into the influence of infrastructure investment strategies on macroeconomic outcomes. Design/Methods/Approach: This study uses a comparative empirical framework, drawing on panel data from the World Bank from 1994 to 2023. Jamovi software is used to statistically analyze the relationship between sectoral purchasing power parity (PPP) investments and gross domestic product (GDP) growth. The analysis focuses on the water, energy, and transportation sectors, examining the magnitude and consistency of investments to evaluate their economic impact. This methodological approach is ideal for identifying sector-specific effects and comparing different national investment strategies. Findings: The study finds that Brazil’s PPP investments are heavily concentrated in energy infrastructure. These investments are large but irregular, which introduces economic volatility and undermines long-term stability. In contrast, China implements a more balanced and consistent investment strategy across the water, energy, and transportation sectors. Transportation investments in China show the strongest positive correlation with GDP growth. However, energy investments exhibit a negative correlation, indicating inefficiencies and resource misallocation. These results underscore the importance of prioritizing infrastructure sectors with higher economic returns while addressing inefficiencies in others. Originality/Value: This research contributes to the existing literature by offering a cross-country, three-decade comparative analysis of sector-specific PPP investments, emphasizing the differential economic outcomes of investment strategies. Unlike previous studies, this research integrates sectoral investment patterns with macroeconomic performance, highlighting the nuanced relationship between investment consistency, sector selection, and economic stability. Practical/Policy implication: The findings inform policymakers and development planners about how to optimize PPP investment strategies. The findings suggest prioritizing transportation infrastructure for higher economic returns, balancing large-scale projects with steady, incremental investments, and strengthening governance and regulatory frameworks to mitigate inefficiencies. The study provides actionable guidance for sustainable infrastructure planning to ensure that PPP investments maximize short- and long-term economic growth.